The role of cooperative mediation in increasing the number of entrepreneurs: Case study of the DKI credit cooperative , - Febrizal Rahmana; Agung Sudjatmoko; Aini Farmani (Management Science Letters, 2019)
Even though the investment sector generally governs economic growth in developed coun-tries. Indonesia's economic growth so far has been dominated by the consumption sector. On the other hand, one of the significant contributors to the investment sector is the entrepreneurs’ role in any country. Therefore, the challenge for Indonesia is to make the entrepreneurs reach substantial contributions. This study investigates on three variables; namely entrepreneurial orientation, cooperatives, and entrepreneurs. Entrepreneurial orientation is the exogeneous variable, cooperative is the mediator variable and, the entrepreneur is the endogenous variable. These three variables are formed into three sub-models and one complete model. Each sub-model is to find out whether the dimensions contribute to each variable, and the entire model is to find out a significant relationship among the variables. The method used is the structural equation model (SEM), with computer software LISREL. This research will produce a breakthrough in how cooperative can mediate from entrepreneurial orientation to entrepreneurs. Besides, the study will deliver how cooperative stakeholders to get some understanding of entrepreneurial orientation so that cooperatives as an institution can persuade members of organizations to become entrepreneurs to be ready to contribute to economic growth. Moreover, the results provide the science of sustainable management on how to apply creativity and innovation to the cooperative organization.